THE INFLUENCE OF SKIMMING TECHNIQUE AND CRITICAL THINKING TOWARD READING COMPREHENSION ACHIEVEMENT OF THE EIGHTH GRADE STUDENTS OF STATE JUNIOR HIGH SCHOOL 50 PALEMBANG - Rusman Roni; Tahrun Tahrun; Dana Listiyanti (ELTE Journal (English Languange Teaching and Education), 2017)
This study aimed at finding out whether or not: (1) there was a significant difference in reading comprehension achievement between the students who have high critical thinking taught by using skimming technique and those of who are taught by using conventional technique; (2) there was a significant difference in reading comprehension achievement between the students who have low critical thinking taught by using skimming technique and those of who are taught by using conventional technique; (3) there was a significant difference in reading comprehension achievement between the students who have high and low critical thinking taught by using skimming reading and those of who are taught by using conventional technique; (4) there was an interaction effect of skimming technique and critical thinking on the students’ reading comprehension achievement. The total number of population was 456 students of the eighth grade students of SMPN 50 Palembang. The sample for this study were 30 students, they was selected as the sample and equally divided into experimental and control groups. By applying pretest and posttest control group design the treatment was only given to the experimental group. The writer took two stage random sampling. The data were analyzed by using three technique: they were the statistical analysis on measuring homogenity and normality data, independent t-test, and two-way ANOVA. Due the research findings, it was found that (1) there was a significant difference in reading comprehension achievement between the students who have high critical thinking taught by using skimming technique and those of who was taught by using conventional technique(0.000<0.05). (2) There was a significant difference in reading comprehension achievement between the students who have low critical thinking taught by using skimming technique and those of who was taught by using conventional technique (0.000<0.05). (3) There was a significant difference in reading comprehension achievement between the students who have high and low critical thinking taught by using skimming technique and those of who was taught by using conventional technique (0.000<0.05). (4) There was an interaction effect of skimming technique and critical thinking on the students’ reading comprehension achievement (0.014<0.05). it means that Skimming technique is effectively used high and low level of students’ critical thinking.Keywords: Reading Comprehension, Skimming Technique, Critical Thinking